Uses and gratifications of smart speakers: modelling the effectiveness of smart speaker advertising. Issue 7 (2nd October 2020) - Lee, Heejun; Cho, Chang-Hoan
Abstract: The purpose of this study is to identify users' motives for using smart speakers from a 'uses and gratification' perspective and to examine the relationship between these motives and the effectiveness of smart speaker advertising. This study has identified four motives for using smart speakers ( virtual interaction for escaping from reality, informational learning, play and relaxation, and pursuit of practicability ). Postulating four advert types for smart speakers—namely contextual, non-contextual, voice-search recommendation, and voice-search listing adverts—this study shows that non-contextual adverts lead to less favourable attitudes than the other three types. Among the four motives for using smart speakers, virtual interaction for escaping from reality and play and relaxation significantly influence attitudes towards smart speaker advertising and brands through the mediation of parasocial relationships. Consumer innovativeness moderates the effect of parasocial relationships on the attitudes towards these adverts and brands. The theoretical and practical implications of smart speaker advertising are discussed.